Education is Forbidden : The Effect of the Boko Haram Conflict on Education in North-East Nigeria - Bertoni, Eleonora (Elsevier, 2020)
This paper quantifies the impact of the Boko Haram conflict on various educational outcomes of individuals living in North-East Nigeria during the period 2009–2016. Using individual panel fixed-effects regressions and exploiting over-time and cross-village variation in conflict intensity, we show that conflict reduces school enrollment. The negative effect is larger for children who are no longer of mandatory school age. We do not find differential effects by gender, religion, or type of residential location. Additional results from a difference-in-differences estimation strategy indicate that conflict reduces the years of education completed.